2000
DOI: 10.1659/0276-4741(2000)020[0042:lccbai]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Land Cover Changes Between 1958 and 1986 in Kalu District, Southern Wello, Ethiopia

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
118
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(126 citation statements)
references
References 20 publications
7
118
0
1
Order By: Relevance
“…Different land use/land cover studies for some parts of Ethiopia indicate that croplands have expanded at the expense of natural vegetation, including forests and shrublands [12,66,68,[70][71][72][73][74] while Tekle and Hedlund [75] reported increases in the size of open areas and settlements at the expense of shrublands and forests. Unlike many of the findings in land use/cover studies in Ethiopia, there have been almost no observed changes in the overall amount of area used for agriculture for about the last fifty years with increasing human and livestock population in the Koga catchment resulting in soil degradation due to over exploitation and erosion from the ploughed fields.…”
Section: Discussionmentioning
confidence: 99%
“…Different land use/land cover studies for some parts of Ethiopia indicate that croplands have expanded at the expense of natural vegetation, including forests and shrublands [12,66,68,[70][71][72][73][74] while Tekle and Hedlund [75] reported increases in the size of open areas and settlements at the expense of shrublands and forests. Unlike many of the findings in land use/cover studies in Ethiopia, there have been almost no observed changes in the overall amount of area used for agriculture for about the last fifty years with increasing human and livestock population in the Koga catchment resulting in soil degradation due to over exploitation and erosion from the ploughed fields.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary particularly in the highlands of Ethiopia in which population pressure is intense resulted for resource erosion and degradation (Grepperud 1996). Likewise, elsewhere in many part of Ethiopian high lands, pressure associated with populations has argued negative implication on forest land, grazing land, barren land, riparian vegetation and farm land (Tekle and Hedlund 2000). It is true to Beressa watershed where rapidly growing of population brought shortage of land, removal of forest cover and soil erosion and land degradation.…”
Section: Cause Of Land Use and Land Cover Change Dynamicsmentioning
confidence: 99%
“…It is located in an altitude between 1705 and 3000 m. The major soil classifications are Camisoles, Phaeozems, and Litho sols [13]. Mean annual temperatures range between 15 and 20°C.…”
Section: Site Descriptionmentioning
confidence: 99%
“…Mean annual temperatures range between 15 and 20°C. Annual rainfall, which is heavy during the summer months (June-August), ranges between 800 and 1200 mm [13].…”
Section: Site Descriptionmentioning
confidence: 99%